Development and Validation of a UV-Spectrophotometric Method for Determination of Vildagliptin and Linagliptin in Bulk and Pharmaceutical Dosage Forms (Bangladesh Pharmaceutical Journal, 2015)
The present study was undertaken to develop a spectrophotometric method for determination of vildagliptin and Linagliptin in pharmaceutical dosage forms. This paper describes a simple, rapid, accurate and precise UVspectrophotometric method for the assay of vildagliptin and linagliptin in bulk and marketed tablet dosage forms. The validation of the developed method was carried out according to ICH guidelines with respect to linearity, precision, accuracy, specificity, limit of detection and limit of quantification. Calibration curves were obtained in the concentration range of 8-32 ?g/ml for vildagliptin and 5-25 ?g/ml for linagliptin with good correlation coefficients (r=0.999). The precisions of the new method for both drugs were less than the maximum allowable limit (%RSD < 2.0) specified by the USP, ICH and FDA. Therefore, the method was found to be an accurate, reproducible and sensitive for analysis of vildagliptin and linagliptin in pharmaceutical dosage forms.Bangladesh Pharmaceutical Journal 18(2): 163-168, 2015